PROMOSI KESEHATAN DENGAN MEDIA LEAFLET TERHADAP PENGETAHUAN TENTANG CARA MENJAGA KESEHATAN GIGI DAN MULUT PADA SISWA SEKOLAH DASAR KELAS 5 SDN 05 PONTIANAK UTARA KOTA PONTIANAK - Haryani, Nike; Damhuji, Damhuji; Herlina, Rita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
School-aged children are a group that is vulnerable to dental and oral health problems. Dental and oral health is important to maintain from an early age to prevent disorders of the teeth and their supporting tissues, the results of research at SDN 05 Pontianak Utara showed that students' knowledge, attitudes, and behavior were still very low. The initial survey found that only 30% of students knew the right time to brush their teeth, 93% did not know when to replace their toothbrush, and 80% did not know the importance of regular dental check-ups, this study aims to determine whether health promotion using leaflet media can improve students' knowledge about how to maintain dental and oral health. This study used a pre-experimental method with a one group pretest-posttest design. The number of respondents was 90 5th grade students of SDN 05 Pontianak Utara who were selected using a total sampling technique. The research instrument was a negative question questionnaire consisting of 15 multiple-choice questions. The questionnaire was given twice, namely before (pretest) and after (posttest) the health promotion was carried out. The results of this study showed a significant increase in students' knowledge before health promotion with leaflet media, students' knowledge was in the poor knowledge category of 63 students (70%) after health promotion with leaflet media, students' knowledge was in the good category of 73 students (81%). The conclusion of this study is that the level of students' knowledge after being given health promotion became good and leaflet media proved effective in increasing the knowledge of fifth grade students of SDN 05 North Pontianak about how to maintain dental and oral health